2005
DOI: 10.1021/jp052132q
|View full text |Cite
|
Sign up to set email alerts
|

The17O Hyperfine Interaction in V17O(H217O)52+and Mn(H217O)62+Determined by High Field ENDOR Aided by DFT Calculations

Abstract: The 17O hyperfine interaction of the water ligands and the V=O oxygen in the vanadyl aquo complex and of the water ligands in the Mn2+ aquo complex in a frozen solution were determined by W-band (95 GHz) electron-nuclear double resonance (ENDOR). Orientation selective ENDOR spectra of the vanadyl complex exhibited two distinct signals assigned to the vanadyl oxygen and the water ligands. The assignment of the signals was done based on the orientation of the principal axis system of the hyperfine interaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 53 publications
9
27
0
Order By: Relevance
“…This assignment is consistent with an earlier W-band ENDOR study of the vanadyl aqua complex that gave A = 10 MHz for the oxo-oxygen and approximately 5 MHz for the equatorial oxygen atoms. [16] Earlier density functional theory (DFT) calculations on 6À gave a significantly higher spin density on the terminal oxygen, consistent with this assignment. [17] Both 17 O and 95 Mo X-and W-band HYSCORE signals had a significant width (2-3 MHz) that could be either due to anisotropic hyperfine couplings or due to a distribution of isotropic hyperfine couplings (or a combination of both).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…This assignment is consistent with an earlier W-band ENDOR study of the vanadyl aqua complex that gave A = 10 MHz for the oxo-oxygen and approximately 5 MHz for the equatorial oxygen atoms. [16] Earlier density functional theory (DFT) calculations on 6À gave a significantly higher spin density on the terminal oxygen, consistent with this assignment. [17] Both 17 O and 95 Mo X-and W-band HYSCORE signals had a significant width (2-3 MHz) that could be either due to anisotropic hyperfine couplings or due to a distribution of isotropic hyperfine couplings (or a combination of both).…”
supporting
confidence: 52%
“…Therefore we assign it to a VO 2 + species that originates from [PV O hyperfine couplings is attributed to fast exchange with the water solvent. [16] Since species II originates from isomers with distal vanadium atoms (Figure 1), it is therefore reasonable to assume that species I forms from the isomers with the proximal vanadium atoms.…”
mentioning
confidence: 99%
“…In this case IH, 2H and ~70 ENDOR can be applied. For the latter, however, the signal-to-noise ratio may require long accumulations times for accurate results [35].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a 17 O a iso value of the same order was recently observed by some of us [18] . [19] This comparison strongly suggests that excess electrons in the blue rutile sample are (at 4 K) largely localized over a single Ti ion, which bears strong similarities to a genuine Ti 3+ molecular cation. The smaller 17 O hfi responsible for the signal in the (+ , + ) quadrant of the HYSCORE spectrum ( 17 O-2) can be interpreted as arising from the interaction between the unpaired electron in the Ti 3d xy orbitals and the axially coordinated oxygen atoms.…”
mentioning
confidence: 89%
“…The 17 O hfi parameters are expected to be highly dependent on the coordination position of the O ligand and in the case of molecular aqua vanadyl cations values of about 2 MHz have been predicted for axially coordinated water. [19] In summary, this initial study on the nature of reduced states in TiO 2 has shown that stable Ti 3+ ions can be generated in the bulk of TiO 2 by a direct and simple synthetic method. The 17 O HYSCORE spectra of such Ti 3+ ions allowed the spin [a] Unresolved.…”
mentioning
confidence: 90%